THE SEMIOTIC ANALYSIS OF SAM SMITHâ€™S PERFORMANCE OF â€œUNHOLYâ€™S SONGâ€ AT THE GRAMMY AWARD 2023 - Pasaribu, Arsen Nahum; Marbun, Leriana; Sembiring, Rony Arahta (Institut Agama Islam Negeri Palopo, 2023)
The purpose of this research is to describe and examine the semiotic process and the message that implied on Sam Smith ft Kim Petrasâ€™ performance of â€œUnholy Songâ€ in Grammy Awards 2023. The semiotic approach is used to identify and to analyse the data which focuses on Sign/Representament (icon, index, symbol), Object (Qualisign, Sinsign, Legisign) and Interpretant (Rheme-Decisign, Argument). This study employed qualitative research with a descriptive design as the data were collected in the form of several images. In analysing data, the writer watched the performancesâ€™ videos, captured the videoclips into the 31 images, and analysed the data with the triangle meaning of Pierceâ€™s theory. Based on the result finding, there are 15 icons, 6 indexes, 29 symbols, 31 qualisigns, 16 sinsigns, 20 legisigns, 21 rhemes, 5 decisigns and 2 arguments. The writer can conclude that the most prominent aspect is qualisign, especially for the colour, red and black. Red represents anger and black represents power and darkness. Qualisign is the dominant aspect because Sam Smith use colour more to convey messages and signs to people.